Safe Transitions and Congregate Living in the Age of COVID‐19: A Retrospective Cohort Study. Issue 9 (18th August 2021) - Boyle, Christopher A; Ravichandran, Urmila; Hankamp, Valerie; Ilbawi, Nadim; Conway‐Svec, Coleen; Shifley, Diane; Hensing, Thomas; Kim, Susan; Halasyamani, Lakshmi
Abstract : BACKGROUND: COVID‐19 represents a grave risk to residents in skilled nursing facilities (SNFs). OBJECTIVE: To determine whether establishment of an appropriate‐use committee was associated with a reduction in SNF utilization. DESIGNS, SETTING, AND PARTICIPANTS: Retrospective cohort study at NorthShore University HealthSystem, a multihospital integrated health system in northern Illinois. Participants were patients hospitalized from March 19, 2019, to July 16, 2020. INTERVENTION: Creation of a multidisciplinary committee to assess appropriateness of discharge to SNF following hospitalization. MAIN OUTCOME AND MEASURES: Primary outcome was total discharges to SNFs. Secondary outcomes were new discharges to SNFs, readmissions, length of stay (LOS), and COVID‐19 incidence following discharge. RESULTS: Matched populations pre and post intervention were each 4424 patients. Post intervention, there was a relative reduction in total SNF discharges of 49.7% (odds ratio [OR], 0.42; 95% CI, 0.38‐0.47) and in new SNF discharges of 66.9% (OR, 0.29; 95% CI, 0.25‐0.34). Differences in readmissions and LOS were not statistically significant. For patients discharged to a SNF, 2.99% (95% CI, 1.59%‐4.39%) developed COVID‐19 within 30 days., compared with 0.26% (95% CI, 0.29%‐0.93%) of patients discharged to other settings ( P < .001). CONCLUSION: Implementing a review committee to assess for appropriateness of SNF use after a hospitalization during the COVID‐19 pandemic is highly effective. There was no negative impact on safety or efficiency of hospital care, and reduced SNF use likely prevented several cases of COVID‐19. This model could serve as a template for other hospitals to reduce the risks of COVID‐19 in SNFs and as part of a value‐based care strategy.